Implementation of The Student Team Achievement Division (STAD) to Develop Student Skills in Explaining Orally Natural Phenomena - Rubaeah, Siti; Gaffar, Muhammad Andriana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
According to Melian O.H & Solihat M.R (2019), speaking is an essential skill in English, where speakers can express ideas, opinions, responses, and information. Problems that arise in learning to speak during a pandemic. These problems include more time for students to practice speaking, lack of communication, and lack of cooperation between other students. This study uses a qualitative method. The approach used is classroom action research. To collect data, researchers used observation, field notes, and interviews. This research was conducted in two stages, namely, cycle one and cycle two. This research was conducted at Mekar Arum High School. The research participants were students of class XI IPS-2, totalling 31 students. Based on the research results, researchers can conclude that implementing the Student Team Achievement Division (STAD) can be used as one of the methods of learning speaking skills. This can be proven by findings that show the development of students' speaking activities. Based on research on students' opinions about the application of STAD, students like this learning method. Students gave positive answers and said that the presentation activities in this learning method gave them public speaking training and trained their confidence in public speaking.